2022
DOI: 10.1186/s12888-022-04249-8
|View full text |Cite
|
Sign up to set email alerts
|

Autistic children and adolescents with frequent restricted interest and repetitive behavior showed more difficulty in social cognition during mask-wearing during the COVID-19 pandemic: a multisite survey

Abstract: Background The public health measures enacted in order to control the coronavirus disease (COVID-19) pandemic have caused considerable changes to daily life. For autistic children and adolescents, adapting to the “new normal,” including mask-wearing, may be difficult because of their restricted interest and repetitive behavior (RRB) characteristics. We aimed to examine the relationships between RRB characteristics and the impact of mask-wearing on their social communications during the pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In terms of COVID-specific behavior such as wearing masks, regular hand washing etc., our study yielded mixed findings. While some children embraced the precautions, others found it difficult to adhere to them, and this may be due to underlying sensory sensitivities or a difficulty in adapting to novel routines ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of COVID-specific behavior such as wearing masks, regular hand washing etc., our study yielded mixed findings. While some children embraced the precautions, others found it difficult to adhere to them, and this may be due to underlying sensory sensitivities or a difficulty in adapting to novel routines ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The specific educational setting of a child must be appreciated when evaluating mask-wearing, alongside any additional needs that children may have. 29,36,45,48,54,63 Literature has shown that accommodations can be made for specific populations of children who may experience additional barriers to mask-wearing, such as children with hearing loss. Lalonde et al 45 demonstrated that adults and children with normal hearing and children with bilateral hearing loss were similarly impacted by face masks, but that accommodations could be made if necessary.…”
Section: Around the Nose Bendy Bitmentioning
confidence: 99%
“…The specific educational setting of a child must be appreciated when evaluating mask‐wearing, alongside any additional needs that children may have 29,36,45,48,54,63 . Literature has shown that accommodations can be made for specific populations of children who may experience additional barriers to mask‐wearing, such as children with hearing loss.…”
Section: Key Findingsmentioning
confidence: 99%
“…Typical face processing (i.e., holistic processing) can be “artificially” disrupted in TDs when a part of the face is concealed, thus leading to face perception difficulties, such as in faces wearing burqa (Kret & de Gelder, 2012), sunglasses (Graham & Ritchie, 2019; Kotsia et al, 2008), ski mask (Manley et al, 2019) and DSFMs (Ventura et al, 2023). This suggests that ASDs could be even more vulnerable than TDs to the massive use of DSFMs in everyday social situations; it has been already shown that DSFMs and lifestyle changes due to public health measures led to more difficulties in social cognition and communication in ASD subjects, particularly the ones presenting higher pre‐pandemic restricted interest and repetitive behavior characteristics (Tamon et al, 2022). Concerning identity and emotion recognition, the only study so far available on ASDs' “identity route” reported disruptive effects of DSFMs for faces initially learned unobstructed; on the contrary, when faces were memorized with DSFMs, ASDs showed an advantage in recognizing masked faces; thus, DSFMs' effect seems to be mediated by the encoding context (Tso et al, 2022).…”
Section: Introductionmentioning
confidence: 99%